The Role of Middle School Principals in Revitalizing Physical Education Classes After the Reduction of Physical Education Periods, From the Perspective of Physical Education Teachers in Wasit Governorate - Hassan Aliwey Abbas (Universitas Hamzanwadi, 2026)
The policy to reduce physical education class hours from two to one hour per week in Wasit Province, Iraq, has posed serious challenges for physical education teachers. However, there is no empirical evidence regarding the role of school principals in facilitating learning following this policy or the obstacles teachers face due to weak administrative support. This study aims to uncover the reality of the principal’s role in facilitating physical education learning, identify differences in perceptions based on school accreditation, analyze the relationship between teachers’ years of service and their perceptions of support, and identify the dominant obstacles faced by teachers. The research method employs a quantitative approach with a descriptive-analytical and comparative-correlational survey design. A purposive sample of 115 physical education teachers from downtown Kut, Wasit, was selected. The instrument consisted of a questionnaire using a 5-point Likert scale that had been tested for content validity (CVI = 0.88) and reliability (Cronbach’s alpha = 0.91). Data analysis utilized descriptive statistics, independent t-tests, and Pearson’s correlation. The role of the principal was classified as low (mean = 2.33). There was a significant difference in perceptions between A-accredited and non-A-accredited schools (t = 2.87; p = 0.005). A moderate negative correlation was found between length of service and perceived support (r = −0.342; p < 0.001). The dominant barriers were: lack of external cooperation (mean = 1.72), lack of budget (mean = 1.76), and the use of physical education class time for other activities (mean = 3.29). The findings are linked to transformational leadership theory (Bass & Avolio, 1994) and occupational socialization theory (Kern & Palmer, 2024). School principals fell short on all four dimensions of transformational leadership. Senior teachers held more negative perceptions due to accumulated experience and burnout. Principal support for physical education at Wasit was very low. A policy review, minimum budget allocation, principal training, and revision of accreditation instruments are needed.